Embedding weight management into safety-net pediatric primary care: randomized controlled trial. - Wylie-Rosett, Judith.; Groisman-Perelstein, Adriana E.; Diamantis, Pamela M.; Jimenez, Camille C.; Shankar, Viswanathan.; Conlon, Beth A.; Mossavar-Rahmani, Yasmin.; Isasi, Carmen R.; Martin, Sarah N.; Ginsberg, Mindy.; Matthan, Nirupa R.; Lichtenstein, Alice H. (2018)
Background: Implementing evidence-based recommendations for treating pediatric overweight and obesity is challenging in low-resource settings. We conducted a randomized controlled trial to evaluate the effects of implementing the American Academy of Pediatrics overweight/obesity recommendations using a Standard Care approach alone or with the addition of an enhanced program in a safety-net pediatric primary care setting (located in Bronx, New York, United States).; Keywords: Weight management, Family-based intervention, Safety net care.; Springer Open.